Anti-OX40 prevents effector T-cell accumulation and CD8+ T-cell mediated skin allograft rejection. - Kinnear, G; Wood, K; Marshall, D; Jones, N (2010)
BACKGROUND: OX40 is a member of the tumor necrosis factor receptor superfamily and is a potent T-cell costimulatory molecule. Although the impact of blockade of the OX40-OX40L pathway has been documented in models of autoimmune disease, the effect on allograft rejection is less well defined. METHODS: The expression of OX40 and impact of OX40 blockade on BM3 T cells (H2Kb-reactive, T-cell receptor-transgenic) after stimulation with alloantigen were assessed in vitro by the incorporation of 3H-thymidine and flow cytometry. In vivo, naïve BM3 or polyclonal CD8+ T cells were transferred into syngeneic recombinase-activating gene(-/-) mice, which received an H2b+ skin allograft with and without anti-OX40. Skin allograft survival was monitored, and the proliferation, number, and phenotype of BM3 T cells were determined using flow cytometry. RESULTS: In vitro allogeneic stimulation of CD8+ T cells resulted in OX40 expression, the blockade of which was found to partially inhibit 3H-thymidine incorporation as a result of increased cell death among activated T cells. Similarly, in vivo, anti-OX40 prevented skin allograft rejection mediated by CD8+ T cells. However, after cessation of anti-OX40 therapy, skin allografts were eventually rejected indicating that tolerance had not been induced. Correlating with the in vitro data, analysis of lymph nodes draining skin allografts revealed that OX40 blockade had no effect on the activation and proliferation of BM3 T cells but rather resulted in diminished effector T-cell accumulation. CONCLUSION: Taken together, these data demonstrate that anti-OX40 attenuates CD8+ T-cell responses to alloantigen by reducing the pool of effector T cells, suggesting that this may be a worthwhile adjunct to preexisting costimulatory molecule-blocking regimens.